Phytochemical Profiling, Antioxidant and Antimicrobial Potentials of Ethanol and Ethyl Acetate Extracts of Chamaenerion latifolium L. - Akmaral Kozhantayeva; Nurgul Tursynova; Ainagul Kolpek; Yelaman Aibuldinov; Arailym Tursynova; Togzhan Mashan; Zhazira Mukazhanova; Manshuk Ibrayeva; Aizhan Zeinuldina; Aisha Nurlybayeva; Zhanar Iskakova; Yerbolat Tashenov (MDPI AG, 2024)
The study investigates the phytochemical profile, antioxidant capacity, and antimicrobial activities of ethanol (ChL-EtOH) and ethyl acetate (ChL-EtOAc) extracts from Chamaenerion latifolium L. (ChL) harvested in Kazakhstan. The ChL-EtOH extract exhibited higher total phenolic (267.48 ± 3.44 mg GAE/g DE) and flavonoid content (24.18 ± 1.06 mg QE/g DE) compared to ChL-EtOAc. HPLC-UV-ESI/MS identified key phenolic acids and flavonoids, including gallic acid, chlorogenic acid, and quercetin 3-glucoside. FT-IR analysis confirmed the presence of characteristic functional groups. Antioxidant assays revealed strong DPPH scavenging and FRAP activities, with ChL-EtOH showing superior results (IC50 = 21.31 ± 0.65 μg/mL and 18.13 ± 0.15 μg/mL, respectively). Additionally, ChL-EtOH displayed notable antimicrobial efficacy against Gram-positive and Gram-negative bacteria, as well as the fungal strain Candida albicans. These findings suggest that ethanol extraction is more efficient for isolating bioactive compounds from ChL, underscoring its potential for pharmaceutical and nutraceutical applications.